Implementation of Fazlur Rahman's Dynamic Approach in Precisely Understanding the Content of the Qur'an: Study of QS Al-Hujurat Verse 9 - Indi Aula Jauharoh; Ahmad Yusam Thobroni; Eka Sulistiyawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article discusses various important aspects of applying Qur'anic values in modern life. This article aims to see the relevance of Islamic teachings in dealing with social issues such as justice in QS. Al-Hujurat verse 9 by using Fazlur Rahman's dynamic approach in an effort to explore the understanding of the verse with precision. This literature research uses descriptive-qualitative method. The data is obtained from representative literature sources and then content analysis is carried out and then concluded. The results showed that Fazlur Rahman's dynamic approach seeks to combine religious texts with the context of human history in maintaining the relevance of Islam as a religion that can adapt to the dynamics of time and place (double movement). This shows that Islam with its universal values can offer solutions to the various challenges of modern life through a flexible, just and principled understanding. The moral idea obtained from understanding QS. Al Hujurat verse 9 is that reconciliation between two conflicting groups should be done fairly.